2021
DOI: 10.3389/fcimb.2021.735416
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling of RNF213 Depleted Cells Reveals Nitric Oxide Regulator DDAH1 Antilisterial Activity

Abstract: RNF213 is a large, poorly characterized interferon-induced protein. Mutations in RNF213 are associated with predisposition for Moyamoya disease (MMD), a rare cerebrovascular disorder. Recently, RNF213 was found to have broad antimicrobial activity in vitro and in vivo, yet the molecular mechanisms behind this function remain unclear. Using mass spectrometry-based proteomics and validation by real-time PCR we report here that knockdown of RNF213 leads to transcriptional upregulation of MVP and downregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Recent work characterized the ubiquitin E3 ligase RNF213 as a novel antiviral and antibacterial protein ( 53 56 ). In line with its role as a host defense protein, we observed that RNF213 protein expression, already detectable in naive cells, was further induced by IFN-γ priming in A549 and a human foreskin fibroblast cell line (HFF-1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work characterized the ubiquitin E3 ligase RNF213 as a novel antiviral and antibacterial protein ( 53 56 ). In line with its role as a host defense protein, we observed that RNF213 protein expression, already detectable in naive cells, was further induced by IFN-γ priming in A549 and a human foreskin fibroblast cell line (HFF-1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some years before, Erdmann et al reported a large family in which rare heterozygous mutations in GUCY1A3 and CCT7, the latter encoding a scaffold protein which stabilizes sGC, were associated with premature coronary heart disease [ 23 ]. Interestingly, recent experimental data suggest that the NO pathway is functionally connected at the cellular level to RNF213 , a giant ubiquitin ligase encoded by a major susceptibility gene in MMA [ 24 , 25 ]. Altogether, these data strongly suggest that NO pathway disruption leads to the development of steno-occlusive lesions in various vascular beds, as observed in MMA (homozygous LOF mutations) or coronary heart disease (heterozygous variants).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum proteomics has revealed dysregulated lipid metabolism in both ischemic and hemorrhagic MMD patients, emphasizing its significance in vascular changes [ 22 ].In addition, the characterization of proteins in Moyamoya angiopathy (MMA) between the brain surface and dura mater has identified Filamin A as a potential key player, offering initial insights into MMA’s unique intracranial vasculopathy [ 23 ]. Investigation into RNF213’s role in MMD and antimicrobial activity has highlighted changes in proteins like MVP, CYR61, and DDAH1 upon RNF213 knockdown, suggesting potential connections between RNF213, immune responses, and MMD development, possibly involving nitric oxide production in combating Listeria infection [ 24 ].…”
Section: Proteomicsmentioning
confidence: 99%